Pernikahan Transnasional dan Self Esteem Remaja di Kawasan Wisata Lovina sebagai Sumber Pembelajaran IPS SMP - I Ketut Sukeardana Putra; I Wayan Lasmawan; I Made Pageh (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Transnational marriage has become a growing social phenomenon in tourism areas, including the Lovina Tourism Area, Bali. Intensive interaction between local communities and foreign tourists encourages cross-national marriages, which subsequently affect family dynamics and adolescent development. Adolescence is a crucial phase of identity formation, in which self-esteem plays an essential role. This study aims to explore the forms and dynamics of transnational marriages in Lovina, examine the self-esteem conditions of adolescents exposed to this phenomenon, and analyze its potential as a contextual learning resource for Social Studies (IPS) at the junior high school level. This research employed a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and documentation, involving adolescents, parents in transnational marriages, IPS teachers, and community leaders. The findings reveal that transnational marriages in Lovina are driven by economic factors, emotional relationships, and cultural interactions. Adolescents show varied self-esteem conditions, influenced by social acceptance, family support, and cultural identity negotiation. Furthermore, this phenomenon has strong potential to be integrated into contextual IPS learning to enhance students’ understanding of globalization, cultural diversity, and social dynamics. The study concludes that transnational marriage is not only a social phenomenon but also a valuable local learning resource for meaningful IPS education.